HERMENEUTIKA DALAM STUDI ALQURAN: Analisis Pemikiran Hamid Fahmy Zarkasyi - Tangahu, Deybi Agustin (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2018)
Hermeneutics as a method of interpretation is still a controversial debate among Muslim intellectuals, especially its application in the study of the Qur'an. A method that is a contribution of Western scholars is considered by some circles of thinkers can be an alternative and guarantee in understanding and reveal the intent behind the text of a verse. However, according to Hamid Fahmy Zarkasyi one of the leaders of ISTAC, hermeneutics is a threat to Islamic thought and civilization , even as a conspiratorial agent of the West over Islam. He saw three things that influence hermeneutics as an interpretative theory namely, first, from Greek mythology to Jewish and Christian theology. Second, from a problematic Christian theology to the rationalization and philosophy movement. Third, from philosophical hermeneutics to hermeneutic philosophy. Based on these three things, according to Hamid Fahmy, hermeneutics is full of values ​​and "Incompatible" with the worldview of Islam, so the need to see hermeneutics in the context of life view. In this research, the writer will conduct a more critical and "objective" study, see the plus-minus of Hamid Fahmy Zarkasyi's view of the hermeneutic concept he assumed as a product of life view. Some of the questions on which this hermeneutics concept is based on Hamid Fahmy Zarkasyi's concept of hermeneutics and its implications in the study of the Qur'an? What influenced Hamid Fahmy Zarkasyi's thinking, thus viewing hermeneutics as a concept that contradicts the Islamic worldview?